2019
DOI: 10.1097/spv.0000000000000644
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Floor Disorders After Obstetric Avulsion of the Levator Ani Muscle

Abstract: Objectives With vaginal childbirth, 10% to 30% of women sustain levator ani muscle avulsion. The objective of this study was to estimate the cumulative incidence of prolapse and other pelvic floor disorders (PFDs), comparing vaginally parous women with and without levator avulsion. Methods Parous women enrolled in a longitudinal study were assessed annually for PFDs with the Pelvic Organ Prolapse Quantification Examination (for prolapse) and the Epidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 19 publications
1
40
1
3
Order By: Relevance
“…For example, levator ani avulsions, which are seen in 10e20% of vaginal deliveries, 3,4 are associated with pelvic organ prolapse (POP). 5,6 Levator ani avulsions are also associated with weaker pelvic floor muscles. 7 This finding, along with a computer simulation model showing that pelvic muscle weakness results in progressive uterovaginal prolapse, 8 suggests that pelvic floor muscle strength may be important in the development of PFDs.…”
mentioning
confidence: 99%
“…For example, levator ani avulsions, which are seen in 10e20% of vaginal deliveries, 3,4 are associated with pelvic organ prolapse (POP). 5,6 Levator ani avulsions are also associated with weaker pelvic floor muscles. 7 This finding, along with a computer simulation model showing that pelvic muscle weakness results in progressive uterovaginal prolapse, 8 suggests that pelvic floor muscle strength may be important in the development of PFDs.…”
mentioning
confidence: 99%
“…Episiotomy increases the risk of injury to the levator ani muscle due to distension of the pubococcygeus muscle during the expulsion stage of delivery, 19 negatively influencing the contraction capacity of pelvic floor muscles, something essential for the conservation of urethral closing pressure above bladder pressure for the maintenance of urinary continence. 20 The findings of previous studies on the association between episiotomy and UI after delivery are inconsistent. While some studies suggested increased frequency and intensity of the complaint of postpartum UI in the presence of episiotomy, 21,22 others concluded that the procedure is not associated with the dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Vor allem die vagi- nal operative Geburt stellt eine Risikosituation dar. Durch eine Entbindung per Forzeps erhöht sich das Risiko eines Levatorabrisses um den Faktor 7, durch eine Vakuumextraktion um den Faktor 4,5 im Vergleich zu einer nicht operativen vaginalen Geburt [13,14].…”
Section: Klinische Bedeutung Des Levatordefektsunclassified